Implementasi Terapi Munajat dalam Konseling Islam untuk Membentuk Kebiasaan Positif Siswa: Studi Kasus di SMP Negeri 1 Siman Ponorogo - Muhammad Sabilillah; Nabilla; M. Nasih Mu'awan; Rifqi Surya Pratama Gunawan (Universitas Muria Kudus, 2026)
This study aims to analyze the effectiveness of munajat therapy as an Islamic counseling technique in fostering positive habits among students in the tahfidz Al-Qur'an program at SMPN 1 Siman Ponorogo. A qualitative case study design was employed, with participants selected through purposive sampling, comprising students actively involved in munajat therapy sessions and Islamic guidance and counseling (BK) teachers. Data were collected through participatory observation, semi-structured interviews, and documentation. Data validity was ensured through source triangulation, technique triangulation, and member checking. Thematic analysis was applied through data reduction, data presentation, and conclusion drawing. The findings demonstrate that munajat therapy effectively shifted students' religious behavioral patterns from the